2015
DOI: 10.3109/13880209.2015.1067232
|View full text |Cite
|
Sign up to set email alerts
|

Baccharis dracunculifoliamethanol extract enhances glucose-stimulated insulin secretion in pancreatic islets of monosodium glutamate induced-obesity model rats

Abstract: Treatment with B. dracunculifolia extracts protected pancreatic islets and prevented the irreversible cellular damage observed in animals in obesity and diabetes models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
(32 reference statements)
2
3
0
1
Order By: Relevance
“…Although we did not measure circulating levels of free fatty acids, a limitation in this report, obese+HESc rats showed strong decrease of triglyceride levels ( Figure 5B ; Table 2 ), which may lead to lower GPR40 activation and consequent decrease of insulin secretion. Our data are further supported by recent findings that methanol extract of Baccharis dracunculifolia (400 mg/Kg/day, 30 days) decreased serum insulin levels in MSG-obese rats subsequent to improved peripheral insulin sensitivity ( Hocayen et al, 2015 ), in spite of insulin oversecretion caused by high parasympathetic activity on pancreatic islets of MSG-obese rodents ( Miranda et al, 2014 ). Authors attributed this effect to the high antioxidant capacity of the extract ( Hocayen et al, 2015 ), a property well-demonstrated by HESc.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Although we did not measure circulating levels of free fatty acids, a limitation in this report, obese+HESc rats showed strong decrease of triglyceride levels ( Figure 5B ; Table 2 ), which may lead to lower GPR40 activation and consequent decrease of insulin secretion. Our data are further supported by recent findings that methanol extract of Baccharis dracunculifolia (400 mg/Kg/day, 30 days) decreased serum insulin levels in MSG-obese rats subsequent to improved peripheral insulin sensitivity ( Hocayen et al, 2015 ), in spite of insulin oversecretion caused by high parasympathetic activity on pancreatic islets of MSG-obese rodents ( Miranda et al, 2014 ). Authors attributed this effect to the high antioxidant capacity of the extract ( Hocayen et al, 2015 ), a property well-demonstrated by HESc.…”
Section: Resultssupporting
confidence: 90%
“…For instance, catechin-derivatives like ( epi )gallocatechin-( epi )gallocatechin- O -gallate, which is present in our HESc extract ( Table 1 ), were shown to promote insulin secretion by improving β-cell mitochondrial function, in addition to other effects like antioxidant, antiinflammatory, and glucotoxicity prevention ( Cai and Lin, 2009 ). Nevertheless, HESc-treated obese rats had reduced serum insulin levels ( Figure 6E ), in spite of a higher ex vivo insulin release response under hyperglycemic conditions ( Figure 7A ), very similar to the effects of Baccharis dracunculifolia methanol extract on MSG-obese rats ( Hocayen et al, 2015 ). This particular set of data is suggestive of a role for HESc as an activator of peripheral pathways evoked either by recovery of peripheral insulin sensitivity ( Figure 6F ), or by lowering of serum lipids ( Figure 5 ), which may promote decreased in vivo insulin release in our obese+HESc rats.…”
Section: Resultssupporting
confidence: 62%
“…There are many approaches to efficiently decrease blood glucose level such as promoting insulin secretion [24], inhibiting glucose absorption [25], stimulating glucose uptake by tissues [26] and increasing insulin sensitivity [27]. Insulinotropic agents such as glibenclamide, stimulate insulin secretion and dramatically decrease blood glucose level in both normal and diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Baccharis dracunculifolia , popularly known in Brazil as alecrim-do-campo (field rosemary) or vassourinha do campo, is a medicinal plant used to treat human disease conditions and from which green propolis is produced by honeybees [5,6,7]. Several biological properties related to B. dracunculifolia , including antidiabetic [8], anti-inflammatory [7], bactericidal [9], and antioxidant [10] activities, have been reported in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%